2015
DOI: 10.1186/s40317-015-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Home range, habitat use, and movement patterns of non-native Burmese pythons in Everglades National Park, Florida, USA

Abstract: Background: Studies on the spatial ecology of invasive species provide critical information for conservation managers such as habitat preferences and identification of native species at risk of predation. To understand the spatial ecology of non-native Burmese pythons (Python molurus bivittatus), now well-established in Everglades National Park and much of South Florida USA, we radio-tracked 19 wild-caught adult pythons, 16 with VHF tags during 2006 through 2009 and 3 by GPS tags between 2010 and 2011. Our goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 55 publications
(71 reference statements)
2
45
1
Order By: Relevance
“…Among squamates, only large lizards such as blue-tongue skinks and monitor lizards have been tracked using GPS tags [e.g., 16,17]. Hart et al [18] reported on the first preliminary application of GPS technology in a large constrictor, the Burmese python (Python bivitattus). This was the first documented GPS application in any snake.…”
Section: Open Accessmentioning
confidence: 99%
See 4 more Smart Citations
“…Among squamates, only large lizards such as blue-tongue skinks and monitor lizards have been tracked using GPS tags [e.g., 16,17]. Hart et al [18] reported on the first preliminary application of GPS technology in a large constrictor, the Burmese python (Python bivitattus). This was the first documented GPS application in any snake.…”
Section: Open Accessmentioning
confidence: 99%
“…Many large constrictors are considered threatened or declining in their native range [20][21][22], whereas other species have become invasive [23], and management of both invasive and imperiled large constrictors would benefit from an improved understanding of their spatial ecology. VHF telemetry has been used to study large constrictor behavior and ecology around the world, including studies on a variety of taxa (e.g., pythons, boas, and anacondas) in a number of different countries (e.g., Argentina, Australia, Bangladesh, South Africa, USA, and Venezuela) [18,[24][25][26][27][28][29][30]. Many of these VHF studies yielded infrequent, irregularly timed, and predominantly daytime locations, and increasing the frequency and regularity of VHF locations in studies of snakes is often difficult due to logistical constraints (e.g., long time to manually record a VHF fix, workload, site inaccessibility, safety-particularly when tracking at night, etc.)…”
Section: Open Accessmentioning
confidence: 99%
See 3 more Smart Citations